Karuppaṉēntiraṉ iyaṟṟiya Pūrvac Cakkaravartti nāṭakam - Karuppaṉēntiraṉ, Veṅkiṭācala (Koṅku Patippakam, 1975)
Comprises a folk play and folk lore from Kongu Nadu, present day Coimbatore District, Tamil Nadu; transcribed from palm leaf manuscripts.